(untitled) (Journal of Bio-Science, 2014)
Context: Alpha-tocopherol has significant effect on the growth performance and fillet proximate composition of Striped Catfish (Pangasius hypophthalmus). Objectives: To study the effect of DL-alpha tocopheryl acetate on the fillet proximate composition (moisture, crude protein, crude lipid, ash and alpha-tocopherol), survival rate and growth performance (SGR, weight gain, PWG) of P. hypophthalmus. Materials and methods: Striped Catfish were fed with three trial diets (diet-1, diet-2 and diet-3) were prepared by adding different amounts of alpha-tocopheryl acetate (ATA, 0, 90 and 300 mgKg-1 diet), over a period of 122 days. In each pond, 10% of the total fish were randomly selected and individually weighed once every fortnight and growth parameters were determined after each weighing. Moisture, dry matter, crude protein, lipid, ash and alpha-tocopherol of the experimental diets and fish fillet were determined by Conventional procedure, standard test method, micro-kjeldahl method, Bligh and Dyer method, standard methods and chromatographic method, respectively. Results: Fish that were fed 90 mg kg-1 and 300 mg kg-1 ATA supplemented diets had significantly higher growth performance than fish that were fed only farm processed diet (P<0.05). The fillet protein, lipid content and alpha tocopherol level of the fish flesh were increased due to ATA supplementation in diets. The vitamin-E levels in fish fillet reflected dietary ATA levels. These results showed that fish on Diets 2 (supplemented with 90 mgKg-1 ATA) and Diet 3(supplemented with 300 mg kg-1 ATA) had significantly better production and resulted better flesh quality of fish than those on Diet 1 (without ATA supplementation). Conclusion: Scanty information is available on the fillet proximate composition and growth performance of P. hypophthalmus fed with diets containing different amounts of alpha-tocopherol. The present study provides baseline information for establishing improved and profitable cultured system of the fish in impounds water of Bangladesh. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17658 J. bio-sci. 20: 67-74, 2012